2022
DOI: 10.1002/wrna.1709
|View full text |Cite
|
Sign up to set email alerts
|

Partners in crime: Proteins implicated in RNA repeat expansion diseases

Abstract: Short tandem repeats are repetitive nucleotide sequences robustly distributed in the human genome. Their expansion underlies the pathogenesis of multiple neurological disorders, including Huntington's disease, amyotrophic lateral sclerosis, and frontotemporal dementia, fragile X-associated tremor/ ataxia syndrome, and myotonic dystrophies, known as repeat expansion disorders (REDs). Several molecular pathomechanisms associated with toxic RNA containing expanded repeats (RNA exp ) are shared among REDs and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 268 publications
0
6
0
Order By: Relevance
“…Our results demonstrate that the structure-specific properties of short RNAs can induce their liquid-to-solid phase transition in vitro, which can even be observed in vivo. These RNA foci induce the colocalization of RNA binding proteins and suppress the clonogenicity of cells, eventually induce cell death 11 , 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate that the structure-specific properties of short RNAs can induce their liquid-to-solid phase transition in vitro, which can even be observed in vivo. These RNA foci induce the colocalization of RNA binding proteins and suppress the clonogenicity of cells, eventually induce cell death 11 , 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, some RAN translation modifiers of FMR1 mRNA have been described. For instance, RNA helicases such as DDX3X (Linsalata et al , 2019) or DHX36 (Tseng et al , 2021), and others extensively reviewed in Baud et al (Baud et al , 2022)) have been identified as affecting CGG repeats-related RAN translation by facilitating ribosomal scanning via unwinding the structured RNA. Components of the endoplasmic reticulum ER-resident kinase (PERK) signaling pathway were shown to modulate RAN translation under stress conditions (Green et al , 2017), and the activity of another kinase, SRPK1, retains mutated FMR1 mRNA containing CGGexp in the nucleus blocking its transport to the cytoplasm and subsequent translation (Malik et al , 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, different proteins involved in RAN translation regulation reviewed in Baud et al , 2022 were uncovered. However, mechanistic insight into this process remains unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…Many SRSs are genetically unstable and frequently increase or decrease the number of repeated units as a result of replication or/and recombination errors. The genetic expansion of microsatellites in transcribed genomic regions is known to give rise to toxic RNAs in several neuromuscular and neurodegenerative disorders (Baud et al 2022; Ciesiolka et al 2017; Fujino and Nagai 2022; Schwartz et al 2021). For example, the type 1 myotonic dystrophy (DM1) is caused by the expansion of the CTG trinucleotide repeat in the 3’ untranslated region (3’UTR) of DMPK gene (Meola and Cardani 2015; Sznajder and Swanson 2019; Yum et al 2017).…”
Section: Introductionmentioning
confidence: 99%